ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN LAPORAN KEUANGAN DENGAN PERSPEKTIF FRAUD HEXAGON (Studi Empiris Pada Perusahaan LQ-45 Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020) - Anis Nur Wulandari; Rina Trisnawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Financial statements are financial records than provide an overview of performance, company profile and can be useful for most users of financial statements in making economic decisions. The purpose of this study is to analyze financial statemen fraud using a fraud hexagon perspective, by measuring pressure proxied by financial targets, financial stability, and external pressure; capability proxied by the change of directors; opportunities proxied by ineffective monitoring; rationalization; collusion proxied by state-owned enterprises; and arrogance. The sample in this study was the LQ-45 Company which was listed on the Indonesia Stock Exchange (IDX) in 2018-2020. This study used secondary data, namely the company’s annual financial statements. With the purposive sampling method, the companies used in this study were 38 companies from a total 45 companies registered and analyzed with multiple linier regression analysis using the SPSS 25 program. The results of this study found that the measurement of external pressure had a significant effect on financial statement fraud. Meanwhile, the measurement of financial targets, financial stability, change of directors, ineffective monitoring, rationalization, state-owned enterprises, and arrogance haven’t effect on financial statement fraud in lq-45 companies listed on the IDX in 2018-2020.